Non-orthogonal multiple access wireless energy harvesting cooperative system - Xiaoping JIN; Qing WU; Wenchao ZHAI; Jianrong BAO (Dianxin kexue)
Non-orthogonal multiple access (NOMA) has recently attracted wide attention as a promising multiple access technology adopted in 5G cellular networks.In order to improve the spectrum efficiency, coverage and anti-noise performance of NOMA technology, while reduce the energy consumption of the system, a simultaneous wireless information and power transfer (SWIPT) cooperative network uplink NOMA transmission system based on orthogonal index modulation multiple access (IMMA) technology was designed, hereafter was denoted as QIMMA-SWIPT.Specifically, the QIMMA system was formed by multiple remote users, and it improved the spectrum efficiency and anti-noise performance as well as expanded the communication coverage and reduced the energy consumption of the system by decoding and forwarding relay cooperative transmission with SWIPT technology.The theoretical upper bound of the average bit error rate of QIMMA-SWIPT was derived.Simulation and analysis demonstrate that, under the same spectrum efficiency, the bit error rate performance of the cooperative QIMMA-SWIPT system is better than that of the cooperative IMMA-SWIPT and SCMA-SWIPT systems.In addition, the effects of power cut factor and source-to-relay distance on bit error performance were also deeply analyzed.